A curved panel energy harvester for aeroelastic vibration. (1st September 2019) - Shan, Xiaobiao; Tian, Haigang; Chen, Danpeng; Xie, Tao
Highlights: A novel curved panel energy harvester for aeroelastic vibration is proposed. A fluid-structure-electric coupling field is established and experimentally validated. Segmented piezoelectric patches PVDF are more advantageous to improve the performance of the harvester. A sustained output power density of 0.032 mW/cm 3 is harvested by this curved panel harvester. Abstract: This paper presents a novel flutter-induced vibration energy harvester with a curved panel for harvesting energy. A finite element model of the fluid-structure-electric coupling field was established to explore the effects of the airflow velocities, the load resistances, the locating positions and dimensions of the piezoelectric patches polyvinylidene fluoride (PVDF) on both the dynamic response and the energy harvesting performance of this curved panel harvester. Considering the cancellation effect of the opposite polarity charges in the same side of the piezoelectric patch at the same time, the energy harvester of the segmented piezoelectric patches attached to the curved panel was further studied for obtaining the optimal output power. An experimental wind tunnel and prototypes of the curved panel energy harvester were designed and fabricated. The results show that simulation and experimental results are in good agreement, and harvesting performance with the segmented piezoelectric patches is better than that of the continuous ones. The average output power first increase until it attains the maximum value, and then decrease with the external load resistance. A sustained output power density of 0.032 mW/cm 3 is harvested at the airflow velocity of 25 m/s and the external load resistance of 10 MΩ. The present work provides an effective theoretical and experimental basis for further studying energy harvesting and vibration control of airfoil aircrafts.